A Critical Study of Manhaj Tarjih Muhammadiyah and Its Implications in the Implementation of Mahdah Worship in the Land of Papua - Mahsyar, Mahsyar; Khoiri (PT. Anagata Sembagi Education, 2025)
This study examines the manhaj tarjih of Muhammadiyah and its implications for the implementation of worship in the Land of Papua. Manhaj tarjih is an approach used by Muhammadiyah in determining Islamic law based on the Qur'an and Hadith through rational and scientific methods, which aims to provide a moderate understanding and in accordance with the context of the times. In Papua, which is known for its diversity of ethnicities, cultures, and traditions, the implementation of manhaj tarjih faces its own challenges in terms of the diversity of religious practices. Therefore, it is important to understand how Muhammadiyah applies the principles of tarjih in the implementation of worship, especially prayer, zakat, fasting, and hajj, which are often influenced by local customs. This research uses a qualitative approach with literature study methods and interviews with religious leaders and communities in Papua. The results of the study show that although there are variations in the implementation of worship, manhaj tarjih remains the main guideline in determining religious decisions, even though it must be adjusted to local social and cultural conditions. The implications of the implementation of manhaj tarjih are not only in the aspect of worship, but also in forming an inclusive and moderate understanding of religion, as well as strengthening tolerance between religious communities. This research also identifies the challenges faced by Muhammadiyah in Papua, such as differences in local traditions that sometimes contradict the scientific principles applied in manhaj tarjih. Therefore, this study suggests the need for a more sensitive approach to local culture in the application of Islamic teachings in Papua..